Islamic Culture in Purwakarta Regency - Imam Tabroni; Rini Purnama Sari (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2022)
History of Islamic Culture in Purwakarta Regency, West Java since the 17th century has embraced Islam. Previously the people of Purwakarta adhered to the Sunda Wiwitan belief. The entry of Islam in Purwakarta did not escape the role of the First Regent, Singa Perbangsa I, whose territory covered Karawang, Cikampek, and Purwakarta is bordered by Bandung. The name Purwakarta was given on August 23, 1830, or on the 4th of Rabiul awal 1250 Hijriah. The origin of the name Purwakarta is closely related to the spread of Islam and the existence of the Great Mosqu (Masjid Agung), or currently the Great Mosque of Baing Yusuf Purwakarta. On 1830 Cutak attended an assembly at the Pendopo which is currently the Office of the Regent of Purwakarta, during the leadership of Dalem Solawat (R.A. Suryawinata). This study uses a qualitative methodology, data taken through interviews, observations and documentation. and book literacy. Primary data is data regarding the history of Purwakarta Regency. Baeng Yusuf and Mama Sempur, the Grand Mosque and the Regent's Office (Pendopo) Secondary data can be obtained from books and the Internet. The research was conducted in Purwakarta Regency from January 2022 to February 2022 for two months. The purpose of this study was to obtain information about the history of Islamic Culture in Purwakarta Regency. The results obtained are that the people of Purwakarta Regency, West Java, have embraced Islam since the 18th century. Starting from the First Regent of the Singaperbangsa 1, the spread of Islam was then spread by Waliyullah figures, including Baeng Yusuf and Mama Sempur. Evidence of Islamic historical heritage, including the people of Purwakarta Regency until 2022, the majority are Muslims. has the Great Mosque. The Regent's Hall has Islamic nuances and others.